MODIFIED CAPACITOR ASSISTED EXTENDED BOOST QUASI Z-SOURCE INVERTER FOR THE GRID-CONNECTED PV SYSTEM - Hemalatha, N; Ramalingam, Seyezhai (IIUM Engineering Journal, 2019)
A grid-tied, single stage, three phase, PV system provides higher efficiency than a two-stage PV system. This paper presents a three-phase, single stage, grid-connected PV system with MPPT and reactive power injection capability into the grid using modified capacitor assisted extended boost quasi Z-source inverter (MCAEB q-ZSI) as the grid-tied PV inverter. The adaptability of the inverter for irradiance changes and the boost factor control with its shoot-through duty ratio adjustment made it highly recommended for the grid system. The shoot-through control technique like maximum constant boost control with a third harmonic injection enhances the performance of the inverter by reducing the low order ripples and voltage stress. The fuzzy voltage controller is proposed with the capacitor linearization algorithm to regulate the DC-link voltage. The current approach uses a fuzzy controller to control the real and the reactive power injection into the grid. The performance evaluation of the fuzzy and PI grid controller is carried out for the constant irradiance condition and from the investigation, parameters like boost factor (B), the shoot-through duty ratio(Ds), real power (P), reactive power (Q), power factor and harmonics in the current injection are determined. A laboratory setup of the PV powered grid system is implemented, tested and validated with the simulation results. ABSTRAK: Dalam sistem fotovoltaik (PV) yang bersambung dengan satu peringkat, satu sistem elektronik kuasa yang mempunyai keuntungan dan kecekapan yang tinggi diperlukan untuk menginterupasi dengan utiliti tersebut. Dalam makalah ini, kapasitor yang diubah suai dibantu oleh pemacu kuadratik Z-source yang dilanjutkan (MCAEB q-ZSI) bertindak sebagai unit interfacing antara PV dan grid. Penyesuaian penyongsang untuk perubahan sinaran dan kawalan faktor rangsangan dengan pelarasan nisbah tugas menembak membuatnya sangat disyorkan untuk sistem grid. Teknik kawalan menembak seperti kawalan rangsangan berterusan maksimum dengan suntikan harmonik ketiga meningkatkan prestasi penyongsang dengan mengurangkan aruhan pesanan rendah dan tekanan voltan. Pendekatan semasa menggunakan pengawal kabur untuk mengawal suntikan kuasa sebenar dan reaktif ke grid. Penilaian prestasi pengawal grid fuzzy dan PI dilakukan untuk keadaan iradiasi malar dan dari penyiasatan, parameter seperti faktor rangsangan (B), nisbah tugas menembak (Ds), kuasa nyata (P), kuasa reaktif Q), faktor kuasa dan harmonik dalam suntikan semasa ditentukan.